Indoor ozone levels, houseplants and peak expiratory flow rates among healthy adults in Taipei, Taiwan - Chang, Li-Te; Hong, Gui-Bing; Weng, Shao-Ping; Chuang, Hsiao-Chi; Chang, Ta-Yuan; Liu, Chien-Wei; Chuang, Wan-Yu; Chuang, Kai-Jen (Environment international, 2019)
The association between houseplants and indoor air quality improvement has been reported in previous studies. However, the effect of houseplant-emitted isoprene on the association between ozone (O3) formation and respiratory health remains unclear. We recruited 60 adult subjects from 60 houses with or without houseplants (1:1) in Taipei; twelve house visits were conducted in each home throughout 2014. The indoor air pollutants that were measured consisted of particulate matter less than or equal to 2.5 μm in diameter (PM2.5), O3 and isoprene. Peak expiratory flow rate (PEFR) was measured in each study subject during each house visit. Household information was collected by a questionnaire. Mixed-effects models were used to explore the association between indoor air pollution levels and PEFR. We found that the concentrations of O3 and isoprene in houses with houseplants were higher than those in houses without houseplants. In contrast, PM2.5 levels and % predicted PEFR were higher in houses without houseplants than in those with houseplants. Moreover, increased levels of O3 and PM2.5 in houses with houseplants were associated with a decreased % predicted PEFR, especially in the summer. We concluded that increased levels of indoor O3 and PM2.5 were associated with decreased PEFR. The presence of houseplants was associated with indoor O3, isoprene and PEFR variations in the summer. •Indoor O3 and PM2.5 are associated with lung function, especially O3 in summer.•Houseplants may increase indoor isoprene and O3 levels, especially in summer.•Houseplants may reduce indoor PM2.5 levels and improve lung function.